Landslide susceptibility mapping using multiple combination weighting determination: a case study of collector roads in Pingshan County, Hebei Province, China - Li, Hui; Song, Kun; Zhai, Xing; Liang, Mingjia (Frontiers in Earth Science, 2024)
The landslide susceptibility map estimates the quantitative relationship between known landslides and control factors, and it has been used for site selection of infrastructures and geo-disaster management. As landslides and rockfalls occur frequently in mountainous areas due to road construction in Hebei Province, China, the managing government needs to evaluate the vulnerability of geo-disasters in the road slopes to avoid unfavorable site selection for subsequent road constructions. Some typical collector road slopes were used as the study area in Pingshan County, Hebei Province. By analyzing the landslide triggering factors, we determined classification criteria and proposed a comprehensive method for determining the weighting. The respective weighting was calculated by the AHP and CRITIC method, and the combination weighting was determined by the Game Theory method. The landslide susceptibility of collector roads was evaluated and mapped using the ArcGIS platform. The susceptibility map was validated using landslides field investigation. The validation results show the effectiveness of the susceptibility methods given the good percentage of correctly classified landslides. The landslide susceptibility map can have a significant impact on reducing the vulnerability of infrastructure to landslides in Hebei Province, China.